The Role of Digital Transformation in Shaping Economic Growth: A Literature Review (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
Digital transformation has emerged as a key catalyst for driving changes across various global economic sectors. This study aims to review relevant literature on the role of digital transformation in fostering economic growth. Utilizing a literature review approach, the study analyzes the contributions of digital technologies to productivity, innovation, economic inequality, and sustainability. Findings reveal that digitalization significantly enhances productivity through innovation and operational efficiency, yet it may exacerbate the digital divide, particularly in developing nations facing infrastructure and digital literacy challenges. Furthermore, digital technologies hold potential to promote economic sustainability by optimizing supply chains and reducing carbon emissions, although challenges such as the environmental impact of digital devices persist. This study identifies gaps in the literature as a basis for future research, including the role of government policies in supporting inclusive digital growth and sector-specific analyses of digital transformation impacts. Managerial implications highlight the importance of leadership diversity and integrating sustainability strategies into digital transformation initiatives..